SOLUSI PEMIKIRAN DAN ALTERNATIF PEMECAHAN KEMISKINAN MENURUT KONSEP EKONOMI ISLAM - Samsidar Samsidar (AL-IQTISHAD, 2020)
AbstractEconomic Conception of Islam in Alleviating Poverty, issues touching people's lives under the poverty line. For it is expected how the Islamic economy can be a solution and alternative solutions in order to get out of poverty and to improve the standard of living better. Method used normative approach to welfare oriented efforts of human life as a command / duty or efforts to solve poverty is appointed by the arguments, both of which originated from the Qur'an and the Holy Prophet Challenges faced by the Indonesian nation today is not only cope with the economic crisis , but also how the economics empowerment of the people and community empowerment as a strategy to change the paradigm of economic development with a populist economic conglomerate to give opportunities to the widest alternative economic institutions that implement an economic system that is based Islamic law (shari'a economics) , for example BAZIS, Baitul Maal Wat - Tamwil (BMT) and Islamic institutions are playing layer of grass roots is now more a place in the hearts of middle and small enterprises small - bottom, both urban and rural areas.Kata Kunci: Kemiskinan; Ekonomi Islam.